(untitled) (Geografia em Atos (Online), 2019)
The paper introduces an affective approach to the study of territory and territoriality. Previous discussions of ‘territoriality’, it is shown, have commonly focused on symbolic dimensions. Where affect has been addressed, it has been mostly in relation to the ‘topophilic bond’ of people and territory. Instead, the paper suggests understanding both re- and deterritorialization processes as inherently affective. This draws attention to how a series of affective ‘vectors’ –including fear and aconchego – intensify or dampen de- and reterritorializations. Moreover, it sheds new light on the formation of capacities of acting in spatial context. To develop this argument, the paper draws on approaches to affect that are inspired by Gilles Deleuze’s reading of Spinoza. It then uses the examples of fear and what in Portuguese is called aconchego to illustrate some of the analytic questions thus arising. What emerges is an affective cartography that entails understanding power relations as affective, rendering previous distinctions between ‘territory’ and ‘territoriality’ questionable.